Hydrologic comparison of prescriptive and water balance covers - Stock, Caleb Swenson, author; Bareither, Christopher A., advisor; Scalia, Joseph, IV, committee member; Paschke, Mark W., committee member (Colorado State University. Libraries, 2018)
The objective of this study was to compare the water balance of prescriptive and water balance cover (WBC) designs for Larimer County Landfill (LCL) via hydrologic modeling. A prescriptive cover is designed to limit percolation into underlying waste via a low permeability layer, whereas a WBC is designed to limit percolation via storing infiltrated precipitation and subsequently releasing the water through evaporation and transpiration. Guidance on WBC designs in Colorado are based on geographical location of the site and particle-size distribution of the available cover soils. Soil characteristics and engineering properties were determined from exhumed samples for a completed closure phase of LCL (Phase 1) and two borrow areas (Borrow Area 3 and Borrow Area 4). Hydrologic modeling was completed using VADOSE/W to predict the percolation rate through the prescriptive and water balance covers. The wettest ten consecutive years on record with a sufficiently complete meteorological data set (1992-2002) were selected for the analysis. Vegetation parameters were assigned to represent the revegetated state observed in Phase 1 and the natural conditions observed in the borrow areas. Predicted percolation through a prescriptive cover was < 0.1 to 2.2 mm/yr, depending on assumed saturated hydraulic conductivity. Evaporation was the primary process for removing water from the prescriptive cover models. Predicted percolation through the WBC models ranged from 6.3 to 11.3 mm/yr depending on the borrow area soil and vegetation parameters. Transpiration was the primary process for removing water from the WBC models. Within all of the regulatory acceptable cover models' evapotranspiration removed 94 to 102% of the precipitation received during the ten years modeled. Results of this study indicate that either a prescriptive cover with a total thickness of 106.7 cm (3.5 ft) or a WBC with a thickness of 76.2 cm (2.5 ft) will meet regulations for final closure cover at LCL.
Keywords: landfill; closure; water balance cover